2018
DOI: 10.1016/j.ipej.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic patterns in biventricular pacing delivered by second-generation cardiac resynchronization devices

Abstract: BackgroundWith increasing use of cardiac resynchronization therapy (CRT), treating physicians should be familiar with different electrocardiographic (ECG) patterns of left ventricular (LV) lead and biventricular (BiV) pacing. However, there are a few publications on ECG patterns during BiV pacing.PurposeThis study was sought to determine different ECG patterns in patients with BiV pacing.MethodsTwelve-lead ECGs during BiV pacing (right ventricular leads at apex and LV leads in one of the lateral coronary veins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The frontal plane QRS axis has only seldom been assessed in CRT studies, mostly as a preimplantation predictor of response, and with modest and contrasting results 16,18–20 ; the paced QRS axis has also been used to assess the relative contribution of RV and LV pacing at different VV intervals or pacing sites 21,22 . In general, the paced QRS axis has not reached the level of confidence required for its use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frontal plane QRS axis has only seldom been assessed in CRT studies, mostly as a preimplantation predictor of response, and with modest and contrasting results 16,18–20 ; the paced QRS axis has also been used to assess the relative contribution of RV and LV pacing at different VV intervals or pacing sites 21,22 . In general, the paced QRS axis has not reached the level of confidence required for its use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] We found that HBP + CS and TRIPLE configurations, but not HBP alone, yielded additional shortening of The frontal plane QRS axis has only seldom been assessed in CRT studies, mostly as a preimplantation predictor of response, and with modest and contrasting results 16,[18][19][20] ; the paced QRS axis has also been used to assess the relative contribution of RV and LV pacing at different VV intervals or pacing sites. 21,22 In general, the paced QRS axis has not reached the level of confidence required for its use in clinical practice. "Quasi-normal" axis is an original definition that combines both frontal and horizontal planes in a simple way; it suggests a balanced electrical activation of the LV from the right and left sides and from up to down, as observed in normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the q wave in lead I during biventricular pacing is always predictive of loss of LV capture. 27 Thus, analysis of the Q/q wave or a QS complex in lead I may be a reliable way to assess LV capture during biventricular pacing. Less commonly, a q wave is also noted in lead aVL.…”
Section: Lead Imentioning
confidence: 99%
“…During biventricular pacing with the RV lead in the outflow tract, the paced QRS in lead V1 is often negative (QS), while the frontal-plane paced QRS axis is often directed to the right inferior quadrant (right axis deviation). 19,27 Biventricular pacing with the RV lead in the RV septum may still show a QS pattern in V1, but the axis may be located in the left inferior or superior quadrant (Figure 7, panel A).…”
Section: Lead IIImentioning
confidence: 99%
See 1 more Smart Citation